Demotic graffiti and other short texts gathered from many publications : short texts III 1201-2350 - Vleeming, S. P. (Studia Demotica, 2015)
As continuation of the two preceding volumes of 'Short Texts' with demotic votive inscriptions (volume I) and mummy labels (volume II), this volume brings together all but 800 demotic and Greek-demotic graffiti. These are in principle all the graffiti published in periodicals, congress proceedings and colloquia and 'Festschrifts', as well as in monographs that are not exclusively concerned with demotic graffiti (chiefly excavations reports). The texts are presented in topographical order from South to North, with those from a single monument kept together. The texts show the full gamut of themes encountered in demotic graffiti, which are more varied than their reputation would suggest: the commemorative inscriptions often have more to offer than just names and provide information about the careers of the inscribers, occasionally even touching on historical events of a larger scale. Specifically the numerous and variegated graffiti from the stone quarries in Middle Egypt and at Tura and Masara opposite ancient Memphis deserve to be mentioned because many of these texts are published here for the first time. Several clusters of these quarry graffiti belong to the first demotic texts that were recorded in the nineteenth century, and they constitute the only extant copies for many texts that have now been destroyed. In addition, there are some three hundred brief inscriptions on various objects such as coins, hieratic papyri and mummy linen, stelae, sculptors' models and plaques, various vases and amphoras, containers for embalming materials, dishes for the preparation of kyphi, and various other objects.